Compound identification in forensic toxicological analysis with untargeted LC–MS-based techniques. (November 2015) - Oberacher, Herbert; Arnhard, Kathrin
Untargeted LC–MS/MS techniques have become indispensable tools for systematic toxicological analysis. Compound identification is based on the mass spectrometric information obtained, and this may include m/z, isotopic pattern, retention time and fragmentation information. All these different kinds of analytical features can be stored in libraries and databases. Currently, the most competent approach for compound identification involves tandem mass spectral library search. State-of-the-art databases were shown to be sensitive, specific, robust and instrument-independent. Low- and high-resolution instruments can both be used to develop efficient screening workflows. For automated and unattended acquisition of tandem mass spectral data, data-dependent acquisition control is the method of choice. Due to their impressive detection sensitivity, data-independent acquisition techniques are finding increased applicability.